769. Mortality Among Inpatients After the Initiation of 'Treat All' With Dolutegravir in Botswana. (31st December 2020) - Klinger, Amanda E; Kronen, Ryan J; Barak, Tomer; Mophuthegi, Patricia; Makhema, Joseph; Zash, Rebecca; Shapiro, Roger
Abstract: Background: Botswana was the first African country to implement a 'treat all' dolutegravir (DTG)-based treatment program for all adults. We studied whether this transition made a short-term impact on inpatient mortality among people living with HIV (PLWHIV). Methods: From Dec 2015-Nov 2017, data were collected prospectively on all patients admitted to the medical wards of a district hospital in Botswana. Tenofovir/emtricitabine/efavirenz (TDF/FTC/EFV) was the first-line recommended antiretroviral treatment (ART) regimen for all ART-naïve adults with CD4 < 350 until May 2016, when it was replaced by TDF/FTC/DTG without CD4 restriction ('treat all'). Multivariable logistic regression was used to compare mortality by ART regimen. Results: Of 1, 969 patients admitted, 41.5% were PLWHIV and of these 62.9% were on ART prior to admission. Before 'treat all', 160 (58.0%) of 276 PLWHIV were on ART prior to admission, and post-implementation 354 (65.4%) of 541 PLWHIV were on ART prior to admission (p=0.01). Among 315 patients on EFV-based ART and 85 on DTG-based ART prior to admission, demographics were similar (Table 1), except for more recent ART initiation with DTG, and lower median CD4 cell count with DTG (256 vs. 339 cells/mm 3 ). Tuberculosis (TB) and community acquired pneumonia were the leading causes of hospitalization for both regimens. Death occurred in 178 (21.8%) PLWHIV, including 29% not on ART and 19% on any ART (p=0.003). Overall, 38% who initiated ART < 3 months prior to admission died (23.7% DTG, 48.8% EFV), and 36% with CD4 cell count < 50 cells/mm 3 died (42.9% DTG, 30.8% EFV). Fewer deaths occurred among those on EFV (18%) compared with those on DTG (27%). However, controlling for CD4 count and timing of ART start, the risk of mortality among those on DTG and EFV was similar (aRR 1.08, 95% CI 0.62, 1.87). TB was the leading cause of death (40.1% off ART, 31.8% on DTG, 22.2% on EFV). Table 1. Demographics, clinical characteristics, and outcomes of people living with HIV (PLWHIV) admitted to Scottish Livingstone Hospital, stratified by ART regimen prior to admission. Conclusion: We found no improvement in inpatient mortality among PLWHIV during the shift to 'treat all' with DTG-based ART in Botswana. Decreasing high inpatient HIV mortality will require increased testing in the community to detect and treat PLWHIV prior to disease progression, and improved screening for opportunistic infections. Disclosures: All Authors : No reported disclosures